Novel Antimicrobial Compounds as Ophiobolin-Type Sesterterpenes and Pimarane-Type Diterpene From Bipolaris Species TJ403-B1 - Shen, Ling; Liu, Mengting; He, Yan; Al Anbari, Weaam Hasan; Li, Huaqiang; Lin, Shuang; Chai, Chenwei; Wang, Jianping; Hu, Zhengxi; Zhang, Yonghui (Frontiers in Microbiology, 2020)
Six previously undescribed ophiobolin-type sesterterpenes, namely bipolatoxins A–F (1–6), one previously undescribed pimarane-type diterpene, namely 1β-hydroxy momilactone A (7), together with three known compounds, namely 25-hydroxyophiobolin I (8), ophiobolin I (9), and ophiobolin A lactone (10), were isolated and identified from the endophytic fungus Bipolaris sp. TJ403-B1. Their structures with absolute configurations were elucidated on the basis of extensive spectroscopic analyses (including 1D and 2D-NMR and HRESIMS data), single-crystal X-ray diffraction analyses, and comparison of experimental circular dichroism (CD) data. All compounds were evaluated for antimicrobial potential, which indicated that bipolatoxin D (4) showed significant inhibitory activity against Enterococcus faecalis with an MIC value of 8 μg/mL, and ophiobolin A lactone (10) showed significant inhibitory activity against Acinetobacter baumannii and Enterococcus faecalis with MIC values of 8 and 8 μg/mL, respectively.